Swedish sports clubs and events during the covid 19 pandemic impacts and responses - Armbrecht, J.; Lundberg, E.; Pettersson, R.; Zillinger, M. (Crisis Management and Recovery for Events: Impacts and Strategies, 2021)
Sweden has 10 million inhabitants of which more than 30% are members of at least one sports club. Typically, sports clubs are organized under the Swedish Sports Confederation (Riksidrottsförbundet). On a national level, approximately 19,000 sports clubs exist, distributed over 72 specialist sports federations. Each club usually stages one or several sport events every year. For example, specialist sports federations organize all championships at national and international levels. From a sports club perspective, these events constitute important sources of income. From a societal perspective, clubs and events create considerable economic impacts, foster public health, and facilitate integration contributing with substantial social values (Brown et al., 2015; Pettersson & Wallstam, 2017; Wallstam, Ioannides, & Pettersson, 2020). During the Covid-19 pandemic, most governments restricted individuals` possibilities for gatherings and movements. On March 12th the Swedish government responded to the pandemic by limiting the number of participants to events to no more than 500 people. Starting March 29th gatherings were limited to 50 people. During the end of year 2020 and the second virus wave, further actions were taken. The government limited the number of visitors and participants to eight people. These restrictions had considerable negative effects on many sport-related activities, events, and thus clubs.